Case Report: Hemispherotomy in the First Days of Life to Treat Drug-Resistant Lesional Epilepsy - Makridis, Konstantin L.; Prager, Christine; Tietze, Anna; Atalay, Deniz A.; Triller, Sebastian; Elger, Christian E.; Thomale, Ulrich-Wilhelm; Kaindl, Angela M. (Frontiers in Neurology, 2021)
Background: Neonatal drug-resistant epilepsy is often caused by perinatal epileptogenic insults such as stroke, ischemia, hemorrhage, and/or genetic defects. Rapid seizure control is particularly important for cognitive development. Since early surgical intervention and thus a short duration of epilepsy should lead to an optimal developmental outcome, we present our experience with hemispherotomy in an infant at the corrected age of one week. Methods: We report successful hemispherotomy for drug-resistant epilepsy in an infant with hemimegalencephaly at a corrected age of one week Results: The infant was diagnosed with drug-resistant lesional epilepsy due to hemimegalencephaly affecting the left hemisphere. Given congruent electroclinical findings, we performed a left vertical parasagittal transventricular hemispherotomy after critical interdisciplinary discussion. No complications occurred during the surgery. Intraoperatively; 118 ml of red blood cells (30 ml/kg) and 80 ml of plasma were transfused. The patient has been seizure-free since discharge without further neurological deficits. Conclusion: We demonstrate that early epilepsy surgery is a safe procedure in very young infants if performed in a specialized center experienced with age-specific surgical conditions and perioperative management. The specific surgical difficulties should be weighed against the risk of life-long developmental drawbacks of ongoing detrimental epilepsy